Bound to Lose: Physical Incapacitation Increases the Conceptualized Size of an Antagonist in Men - Fessler, Daniel M. T. (Public Library of Science, 2013)
Because decision-making in situations of potential conflict hinges on assessing many features of the self and the foe, this process can be facilitated by summarizing diverse attributes in a single heuristic representation. Physical size and strength are evolutionarily ancient determinants of victory in conflict, and their relevance is reinforced during development. Accordingly, size and muscularity constitute ready dimensions for a summary representation of relative formidability, a perspective paralleled by the notion that social power is represented using envisioned relative size. Physical incapacitation constitutes a significant tactical disadvantage, hence temporary incapacitation should increase the envisioned size and strength of an antagonist. In Study 1, being bound to a chair increased men’s estimates of the size of an angry man and decreased estimates of their own height. Study 2 conceptually replicated these effects: among men for whom standing on a balance board was challenging, the attendant experience of postural instability increased estimates of an angry man’s size and muscularity, with similar patterns occurring at a reduced level among all but those whose equilibrium was apparently unaffected by this task.